Comparison of cognitive‐behavioral therapy and yoga for the treatment of late‐life worry: A randomized preference trial. Issue 12 (27th October 2020) - Brenes, Gretchen A.; Divers, Jasmin; Miller, Michael E.; Anderson, Andrea; Hargis, Gena; Danhauer, Suzanne C.
Abstract: Background: The purpose of this study was to compare the effects of cognitive‐behavioral therapy (CBT) and yoga on late‐life worry, anxiety, and sleep; and examine preference and selection effects on these outcomes. Methods: A randomized preference trial of CBT and yoga was conducted in community‐dwelling adults 60 years or older, who scored 26 or above on the Penn State Worry Questionnaire‐Abbreviated (PSWQ‐A). CBT consisted of 10 weekly telephone sessions. Yoga consisted of 20 biweekly group yoga classes. The primary outcome was worry (PSWQ‐A); the secondary outcomes were anxiety (PROMIS‐Anxiety) and sleep (Insomnia Severity Index [ISI]). We examined both preference effects (average effect for those who received their preferred intervention [regardless of whether it was CBT or yoga] minus the average for those who did not receive their preferred intervention [regardless of the intervention]) and selection effect (which addresses the question of whether there is a benefit to getting to select one intervention over the other, and measures the effect on outcomes of self‐selection to a specific intervention). Results: Five hundred older adults were randomized to the randomized trial (125 each in CBT and yoga) or the preference trial (120 chose CBT; 130 chose yoga). In the randomized trial, the intervention effect of yoga compared with CBT adjusted for baseline psychotropic medication use, gender, and race was 1.6 (−0.2, 3.3), p  = .08 for the PSWQ‐A. Similar results were observed with PROMIS‐Anxiety (adjusted intervention effect: 0.3 [−1.5, 2.2], p  = .71). Participants randomized to CBT experienced a greater reduction in the ISI compared with yoga (adjusted intervention effect: 2.4 [1.2, 3.7], p  < .01]). Estimated in the combined data set ( N  = 500), the preference and selection effects were not significant for the PSWQ‐A, PROMIS‐Anxiety, and ISI. Of the 52 adverse events, only two were possibly related to the intervention. None of the 26 serious adverse events were related to the study interventions. Conclusions: CBT and yoga were both effective at reducing late‐life worry and anxiety. However, a greater impact was seen for CBT compared with yoga for improving sleep. Neither preference nor selection effects was found.